Individualized controlled ovarian stimulation in expected poor-responders: an update - Thor Haahr; Sandro C. Esteves; Peter Humaidan (BMC, 2018)
Abstract Controlled ovarian stimulation with subsequent multi-follicular development continues to be a keystone in ART. Evidence supports an individualized approach to ovarian stimulation, usually involving combinations of ovarian reserve tests, body mass index and age to tailor the exogenous gonadotropin dose, and potentially adjuvant treatment aiming for high safety and a shortening of time to live birth. While stimulation and trigger concepts have been developed successfully in normo- and hyperresponder patients, the poor responder patient remains difficult to manage. However, recent advances in definition and classification of the expected poor ovarian responder patient might enable a more accurate and clinically useful interpretation of new treatment concepts in a more homogenous study population. In the present review, we discuss the classification of the expected poor ovarian responder patient as well as clinically useful measurements of efficacy for controlled ovarian stimulation, and finally, we discuss the evidence for clinical management of patients with expected poor ovarian response, including adjuvant treatments such as growth hormone, androgens, and LH activity. In conclusion, the best available evidence supports that the treatment of the expected poor ovarian response patient should be individualized in all steps of ART, including the choice of GnRH analogue, the gonadotropin type and dose, ovulation trigger, and the possible use of adjuvant therapies.